Is the basal area of maize internodes involved in borer resistance? - Santiago, Rogelio (BioMed Central, 2011)
BACKGROUND: To elucidate the role of the length of the internode basal ring (LIBR) in resistance to the Mediterranean corn borer (MCB), we carried out a divergent selection program to modify the LIBR using two maize synthetic varieties (EPS20 and EPS21), each with a different genetic background. We investigated the biochemical mechanisms underlying the relationship between the LIBR and borer resistance. Selection to lengthen or shorten the LIBR was achieved for each synthetic variety. The resulting plants were analyzed to determine their LIBR response, growth, yield, and borer resistance. RESULTS: In the synthetic variety EPS20 (Reid germplasm), reduction of the LIBR improved resistance against the MCB. The LIBR selection was also effective in the synthetic variety EPS21 (non-Reid germplasm), although there was no relationship detected between the LIBR and MCB resistance. The LIBR did not show correlations with agronomic traits such as plant height and yield. Compared with upper sections, the internode basal ring area contained lower concentrations of cell wall components such as acid detergent fiber (ADF), acid detergent lignin (ADL), and diferulates. In addition, some residual 2,4-dihydroxy-7-methoxy-(2H)-1,4-benzoxazin-3-(4H)-one (DIMBOA), a natural antibiotic compound, was detected in the basal area at 30 days after silking. CONCLUSION: We analyzed maize selections to determine whether the basal area of maize internodes is involved in borer resistance. The structural reinforcement of the cell walls was the most significant trait in the relationship between the LIBR and borer resistance. Lower contents of ADF and ADL in the rind of the basal section facilitated the entry of larvae in this area in both synthetic varieties, while lower concentrations of diferulates in the pith basal section of EPS20 facilitated larval feeding inside the stem. The higher concentrations of DIMBOA may have contributed to the lack of correlation between the LIBR and borer resistance in EPS21. This novel trait could be useful in maize breeding programs to improve borer resistance.